Toward compassionate workplaces: Employers’ and employees’ perspectives on serious illness, dying, death, and grief: Findings from a nationwide online survey in Germany - Helena Kukla; Tobias Lang; Melanie Joshi; Karin Ohler; Golrokh Esmaili; Georg Bollig; Raymond Voltz; Julia Strupp (PLoS ONE, 2026)
Background Experiences of serious illness, dying, death, and grief in the workplace significantly affect employee well-being, productivity, and organizational culture. Despite increasing recognition of their importance, there is limited understanding of workplace perspectives in Germany. This study addresses this gap by examining the attitudes and experiences of employees and employers regarding these issues to inform workplace policies that promote well-being and resilience. Methods We conducted a nationwide representative cross-sectional online survey (n = 1,127) using a self-developed questionnaire with closed and open-ended items. Data were collected from managers and non-managers across multiple sectors to identify key themes, challenges, and opportunities for improving workplace practices. Closed-ended questions were analyzed quantitatively, and open-ended responses qualitatively. Findings More than sixty-three percent (63.1%) of respondents reported having been affected within the past five years. Workplace support was limited, with 42.7% seldom or never receiving managerial support. Informal support from colleagues and managers was more common and often preferred over formal provisions. Employees valued understanding, empathy, and availability, whereas managers emphasized structural measures such as leave policies. Barriers, uncertainties, and a strong need for guidance and training were frequently reported. Employees in smaller companies expressed greater concerns about legal consequences and stronger support needs, while larger organizations more often offered formal guidelines and programs. Conclusions The mismatch between employees’ needs and managerial focus underscores the importance of aligning workplace practices with employee expectations. Training, guidance, and initiatives that integrate psychosocial and structural support could strengthen well-being and enhance organizational resilience.